Comparison Of Plyometrics And Aerobic Exercises On Attention Levels In Young Adults - Kinanti Maura Sandradewi; Endang Kumaidah; Yosef Purwoko; Marijo Marijo (Faculty of Medicine, Universitas Diponegoro, Semarang, Indonesia, 2021)
Background. Plyometrics and aerobic training is a form of exercise that is easily applicable to all people. Plyometrics and aerobic trainings are proven to improve attention level in previous study.Objective. The aim of this study is to compare the effect of plyometrics training and aerobic training on attention level of young adults.Methods. A quasi-experimental study with pre and post test&control group design. The subjects were 54 male, with age range from 18 to 23 years old. Subjects were divided into 3 groups: C (control), EP1 (plyometrics training), and EP2 (aerobic training; with of 20meters multistage shuttle test design) . Both EP groups was given training for 6 weeks, twice a week. The attention level was measured using Attention Networks Test.Results. After 6-weeks of training, attention score in both of experimental groups were better than the control group. In EP1, all of the attention level component which was alerting, orienting, and executive increases significantly (p<0,01). In EP2, only alerting (p<0,01) and executive (p=0,01) increase significantly. Plyometrics training is proven to increase the attention level better than aerobic training, with significant increase in alerting (p=0,012), orienting (p=0,016), and executive (p=0,02)Conclusion. Plyometrics training is proven to increase attention level better than aerobic training in young adults.